Microparacaryum longipedicellatum (Boraginaceae)—a new combination - Sutorý, Karel (Phytotaxa, 2019)
The taxon Paracaryum longipedicellatum Riedl is hereby transferred to the genus Microparacaryum (Popov ex Riedl) Hilger & Podlech. Distinguishing morphological characters based on the sparse inflorescence, longer pedicels, patent indumentum on stems and sparse indumentum on calyx are presented. Its distribution, centered in mountainous provinces of Afghanistan and Pakistan, is documented based on herbarium specimens.